Strategi Adaptasi Perusahaan Biro Tour and Travel dalam Menghadapi Pandemi Covid-19 (Studi Kasus pada Perusahaan Tour and Travel Haji dan Umrah PT. Amanu Izzah Zamzam Sakinah di Kota Surakarta) - Lailatussani Alfiyah; Wibowo Isa (Akademika: Jurnal Keagamaan dan Pendidikan, 2020)
This study is to determine the strategic management used by PT. Amanu Izzah Zamzam Sakinah in theera new normal and to find out the impact of strategic management on the existence of PT. Amanu Izzah Zamzam Sakinah. Referring to the objectives of this study, at least it is hoped that this research can provide several benefits and contributions both theoretically, practically and academically. In this study, using a descriptive qualitative research method with a case study approach. As for the strategies that have been compiled and carried out by PT. Amanu Izzah Zamzam Sakinah itself is a strategy in managerial strategy which is to do work from home, virtual meetings and meetings, coordination with directors, staff and partners from PT. Amanu Izzah Zamzam Sakinah, gave motivation or support to each other, enriched the information from the government of Saudi Arabia and the Ministry of Religion. The impact of the use of strategic management in the new moral era on PT Manu Izzah Zamzam Sakinah is very good and provides positive impact by synergizing with each other in doing work and maintaining companies that live side by side with the current pandemic situation.